2013
DOI: 10.1016/s0212-6567(13)70022-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status in preschool children: current trends of mother's body perception and concerns

Abstract: Despite signs of a positive trend, mothers continue to show difficulty in recognizing the children's nutritional status, so effective public health strategies to increase parents' awareness could be the first step in an effort to prevent childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
5
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 11 publications
2
25
5
2
Order By: Relevance
“…In this context, the appropriate perception of children's nutritional status by their parents (especially their mother) becomes essential for the early recognition of childhood overweight and obesity [810]. Mothers usually have a greater responsibility over children's diet and education, and their perception of child's nutritional status has shown to have an influence on maternal attitudes and practices related to child's food intake [1012].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, the appropriate perception of children's nutritional status by their parents (especially their mother) becomes essential for the early recognition of childhood overweight and obesity [810]. Mothers usually have a greater responsibility over children's diet and education, and their perception of child's nutritional status has shown to have an influence on maternal attitudes and practices related to child's food intake [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Mothers usually have a greater responsibility over children's diet and education, and their perception of child's nutritional status has shown to have an influence on maternal attitudes and practices related to child's food intake [1012]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In children/adolescents with overweight/obesity they were measured by the nutritionist whereas for children/adolescents with healthy-weight these data were self-reported. This could prevent accurate answers regarding these measures in the healthy-weight group, specifically taking into account that research has found that mothers can be unreliable at reporting their child's weight (Aparício et al, 2013;Silva, Junior, Nascimento, Bertoli, & Gallo, Leone, 2016).…”
Section: Discussionmentioning
confidence: 99%